Assessment of full-scale tertiary wastewater treatment by UV-C based-AOPs: removal or persistence of antibiotics and antibiotic resistance genes? - Rodríguez-Chueca, Jorge (2018)
AOPs based on the photolytic decomposition of H2O2 and peroxymonosulfate tested at low dosages (0.05-0.5 mM) and with very low UV-C contact time (4-18 s) demonstrated to be more efficient than UV-C radiation alone on the removal of the analyzed ABs. PMS (0.5 mM) combined with UV-C (7 s contact time) was the most efficient treatment in terms of AB removal: 7 out of 10 ABs detected in the waste water were removed more efficiently than using the other oxidants. In terms of ARGs removal efficiency, UV-C alone seemed the most efficient treatment, although H2O2/UV-C, PMS/UV-C and PMS/Fe(II)/UV-C were supposed to generate higher concentrations of free radicals. The results show that treatments with the highest removal of ABs and ARGs did not coincide, which could be attributed to the competition between DNA and oxidants in the absorption of UV photons, reducing the direct photolysis of the DNA. Whereas the photolytic ABs removal is improved by the generation of hydroxyl and sulfate radicals, the opposite behavior occurs in the case of ARGs. These results suggest that a compromise between ABs and ARGs removal must be achieved in order to optimize wastewater treatment processes.